CEO duality in manufacturing firms in Singapore. - Lim, Yun Pei. (2008)
This study investigated the relevance of CEO-Chairman duality on firm performance for manufacturing firms listed on the Singapore Stock Exchange. In addition, CEO-Chairman duality was examined with respect to the firm size, as measured in net assets. For the purpose of the research, empirical observations were gathered and interpreted accordingly.